RELATIONSHIP OF LIMB POWER TO SWIMMING CAPABILITY IN CATEGORY 6 YEARS AGE ATHLETES - Ferda, Ferda Maulana Hakim (STKIP Muhammadiyah Kuningan, 2024)
In mastering swimming, especially breaststroke, there are many factors that influence it, one of which is leg power. This study aims to determine the relationship between leg power and breaststroke swimming ability of KU 6 Kubang Bali Swimming Club Athletes, Salem District, Brebes Regency. This research is a correlational description research. The research subjects used were KU 6 Kubang Bali Swimming Club Athletes, Salem District, Brebes Regency, totaling 14 athletes. then given tests and measurements on each of the sub-variables. The research instrument is leg power and breaststroke swimming ability. The data analysis technique uses tests and measurements, namely the analysis of correlation coefficient tests, through prerequisite tests, normality tests and linearity tests.The results showed that there was a relationship between leg power and breaststroke swimming ability with rcount of 0.481 and rtable of 0.404. Because rcount is greater than rtable (0.481>0.404). This means that there is a relationship between leg power and breaststroke swimming ability for KU 6 Kubang Bali Swimming Club Athletes, Salem District, Brebes Regency. Thus the alternative hypothesis is accepted.